Desenvolvimento, caracterização e avaliação de atividade in vivo de sistemas de liberação de ativo antiglaucomatoso a partir de filmes de quitosana e condroitina - Aina Liz Alves Cesar (2019)
Glaucoma is the second leading cause of preventable and irreversible blindness in the world, so it is a social impact disease. The preservation of vision and the reduction of damage on the retinal ganglion cell (RGC) and to optic disc are the fundamentals of its therapy, which consists in the topical application of eye drops in order to reduce intraocular pressure (IOP). It is not uncommon, however, the discontinuation of treatment due to the dosing schedule, which involves multiple daily doses and has systemic and/or local adverse effects. An alternative to these problems could be the ophthalmic inserts, a prolonged drug release dispositive that allow, for example, an increase in bioavailability and a consequent reduction on the loss of the asset by tearing and/or by drainage via the lacrimonasal duct. Diminazene (DIZE) is an antiprotozoan drug, but some studies indicates that it has potential as a vasodilator which allows the use in the treatment of other diseases including glaucoma. The hypothesis was raised that one of the metabolites of DIZE, 4-aminobenzamidine dihydrochloride (4-AD), would be responsible for this observed pharmacological action. In this study, two polymers with biodegradable, biocompatible and mucoadhesive characteristics (chitosan - Chs - and chondroitin sulfate - SC) were used to formulate four types of ophthalmic inserts in different polymeric proportions. An analytical method was developed and validated to perform 4-AD assay and release tests. High performance liquid chromatography (HPLC) was the method of choice and validation followed the rules of RDC no 166/2017 of ANVISA and the ICH guide. It was observed that within the established limits (5-25 μg/mL) the method was linear, selective, precise, accurate and robust. The inserts were prepared by the solvent evaporation method and characterized in relation to the hydration potential and the adhesion force, the formulation with the most satisfactory result contained Chs and SC in the proportion 50: 50% (m/m). This insert did not present fragility in the face of swelling and demonstrated to have the greatest mucoadhesion strength among the tested formulations, according to a study carried out according to the method of Hassan and Gallo. Then, the physical-chemical characterization was performed through thermal analysis, infrared spectroscopy and scanning electron microscopy, together, these techniques suggested that the asset was dispersed homogeneously in the polymer matrix. The in vivo test demonstrated that the insert kept the intraocular pressure reduced for at least three weeks, in addition to preventing the death of the RSG when the treated group was analyzed in relation to the control group, which received the placebo insert. Therefore, the formulated device is viable and the active has demonstrated efficacy in glaucoma therapy. Together, this gave the work an innovative character, since the device described could be a more comfortable and effective therapeutic strategy in the treatment of glaucoma.